Pentingnya Pemahaman Dasar-Dasar Perpajakan Dalam Meningkatkan Kepatuhan Wajib Pajak - Yauma Afriyanti; Septian Dwi Cahya; Imel Santika; Dini Vientiany (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Taxpayer compliance plays an important role in supporting state financing. The amount of state revenue from taxes will be greatly influenced by the level of tax compliance. This study aims to conceptually examine the importance of basic understanding in enhancing taxpayer compliance for the public. From various studies available, it is concluded that tax compliance can have a significant role in improving the welfare of society. This research utilizes a qualitative method. The data used in this study are both secondary and primary data.